`1)`
`(x-2)^3+(x+2)^3`
`= x^3-6x^2 + 12x -8 + x^3+6x^2+12x+8`
`= 2x^3 +24x`
`2)`
`(x-1)^3 -(x+1)^3`
`= x^3-3x^2 + 3x-1 -(x^3 +3x^2+3x+1)`
`= x^3 -3x^2 +3x-1 -x^3 -3x^2-3x-1`
`= -6x^2 -2`
`3)`
`(1-x)^3 +(x+3)^3`
`= 1-3x+3x^2 -x^3 +x^3+9x^2 + 27x +27`
`= 12x^2 +24x +28`
`4)`
`(x+2y)^3 -(x-2y)^3`
`= x^3 + 6x^2y + 12xy^2 + 8y^3 -(x^3 - 6x^2y+12xy^2 - 8y^3)`
`= x^3 +6x^2y +12xy^2 +8y^3 -x^3 +6x^2y -12xy^2 + 8y^3`
`= 12x^2y +16y^3`
`5)`
`(y-x)^3 -(2x-y)^3`
`= y^3-3xy^2 + 3x^2y -x^3 -(8x^3 - 12x^2y + 6xy^2 -y^3)`
`= y^3 -3xy^2 + 3x^2y -x^3 -8x^3 +12x^2y - 6xy^2 +y^3`
`= -9x^3 +2y^3 -9xy^2 + 15x^2y`
`6)`
`(2x+y)^3 -2(y-x)^3`
`= 8x^3 + 12x^2y + 6xy^2 +y^3 -2(y^3 - 3xy^2 + 3x^2y-x^3)`
`= 8x^3 +12x^2y + 6xy^2 +y^3 -2y^3 +6xy^2 - 6x^2y + 2x^3`
`= 10x^3 -y^3 +6x^2y +12xy^2`
`7)`
`(2x-3)^3 -2x(2x+1)^2`
`= 8x^3 - 36x^2 + 54x - 27 -2x(4x^2 + 4x+1)`
`= 8x^3 -36x^2 + 54x -27 -8x^3 - 8x^2 -2x`
`= -44x^2 + 52x -27`
`8)`
`(3x-1)^3 -27x^2(x+1)`
`= 27x^3 - 27x^2 + 9x -1 -27x^3 -27x^2`
`= -54x^2 +9x-1`
`9)`
`(2x+1)^3 -8x(x-1)^2`
`= 8x^3 + 12x^2 + 6x +1 -8x(x^2-2x+1)`
`= 8x^3 +12x^2 +6x +1 - 8x^3 +16x^2 -8x`
`= 28x^2 -2x +1`